THE STRATEGY ANALYSIS FOR DEVELOPMENT OF INDONESIAN NAVY COMBAT CAPABILITIES - Made Suwandiyana; Ahmadi Ahmadi; Zainal Syahlan (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
Warships are one of the main components of the Navy having the main task of maintaining national security and defense at sea. Based on a research study in 2019, the age of warships over 30 years is 60% which has an impact on the decline in the performance of warships. A strategy is needed to improve the performance of warships to achieve the implementation of its main duties and functions as a means of defense. To solve this problem, it is necessary to pay attention to and consider several aspects, both internally and externally through the dynamic system approach method with the Causal Loop Diagram (CLD) model which emphasizes the impact of dynamic aspects associated with influential cause and effect problems. The selected strategies include human resource development, operational readiness, capability development, and increased interoperability. Keywords : CLD, STELLA, System Dynamiic.